b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
b(b(x)) → d(c(x))
c(c(x)) → d(d(d(x)))
c(x) → g(x)
d(d(x)) → f(c(x))
d(d(d(x))) → c(g(x))
f(x) → g(a(x))
g(x) → b(a(d(x)))
g(g(x)) → c(b(x))
↳ QTRS
↳ QTRS Reverse
↳ QTRS
↳ QTRS Reverse
↳ DependencyPairsProof
b(b(x)) → d(c(x))
c(c(x)) → d(d(d(x)))
c(x) → g(x)
d(d(x)) → f(c(x))
d(d(d(x))) → c(g(x))
f(x) → g(a(x))
g(x) → b(a(d(x)))
g(g(x)) → c(b(x))
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
b(b(x)) → d(c(x))
c(c(x)) → d(d(d(x)))
c(x) → g(x)
d(d(x)) → f(c(x))
d(d(d(x))) → c(g(x))
f(x) → g(a(x))
g(x) → b(a(d(x)))
g(g(x)) → c(b(x))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ QTRS
↳ DependencyPairsProof
b(b(x)) → d(c(x))
c(c(x)) → d(d(d(x)))
c(x) → g(x)
d(d(x)) → f(c(x))
d(d(d(x))) → c(g(x))
f(x) → g(a(x))
g(x) → b(a(d(x)))
g(g(x)) → c(b(x))
C(c(x1)) → D(d(d(x1)))
G(x1) → B(x1)
G(x1) → D(a(b(x1)))
G(g(x1)) → B(c(x1))
C(c(x1)) → D(x1)
G(g(x1)) → C(x1)
B(b(x1)) → C(d(x1))
C(c(x1)) → D(d(x1))
F(x1) → G(x1)
B(b(x1)) → D(x1)
C(x1) → G(x1)
D(d(x1)) → C(f(x1))
D(d(d(x1))) → G(c(x1))
D(d(x1)) → F(x1)
D(d(d(x1))) → C(x1)
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
C(c(x1)) → D(d(d(x1)))
G(x1) → B(x1)
G(x1) → D(a(b(x1)))
G(g(x1)) → B(c(x1))
C(c(x1)) → D(x1)
G(g(x1)) → C(x1)
B(b(x1)) → C(d(x1))
C(c(x1)) → D(d(x1))
F(x1) → G(x1)
B(b(x1)) → D(x1)
C(x1) → G(x1)
D(d(x1)) → C(f(x1))
D(d(d(x1))) → G(c(x1))
D(d(x1)) → F(x1)
D(d(d(x1))) → C(x1)
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
C(c(x1)) → D(d(d(x1)))
G(x1) → B(x1)
G(g(x1)) → B(c(x1))
C(c(x1)) → D(x1)
G(g(x1)) → C(x1)
B(b(x1)) → C(d(x1))
C(c(x1)) → D(d(x1))
F(x1) → G(x1)
B(b(x1)) → D(x1)
D(d(x1)) → C(f(x1))
D(d(d(x1))) → G(c(x1))
C(x1) → G(x1)
D(d(x1)) → F(x1)
D(d(d(x1))) → C(x1)
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
G(x1) → B(x1)
G(g(x1)) → B(c(x1))
C(c(x1)) → D(x1)
G(g(x1)) → C(x1)
B(b(x1)) → C(d(x1))
C(c(x1)) → D(d(x1))
F(x1) → G(x1)
B(b(x1)) → D(x1)
D(d(x1)) → F(x1)
D(d(d(x1))) → C(x1)
Used ordering: Polynomial interpretation [25]:
C(c(x1)) → D(d(d(x1)))
D(d(x1)) → C(f(x1))
D(d(d(x1))) → G(c(x1))
C(x1) → G(x1)
POL(B(x1)) = 6 + 4·x1
POL(C(x1)) = 8 + 4·x1
POL(D(x1)) = 4·x1
POL(F(x1)) = 13 + 4·x1
POL(G(x1)) = 8 + 4·x1
POL(a(x1)) = 2
POL(b(x1)) = 6 + x1
POL(c(x1)) = 6 + x1
POL(d(x1)) = 4 + x1
POL(f(x1)) = 2
POL(g(x1)) = 6 + x1
g(x1) → d(a(b(x1)))
f(x1) → a(g(x1))
b(b(x1)) → c(d(x1))
d(d(d(x1))) → g(c(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
g(g(x1)) → b(c(x1))
d(d(x1)) → c(f(x1))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
C(c(x1)) → D(d(d(x1)))
C(x1) → G(x1)
D(d(d(x1))) → G(c(x1))
D(d(x1)) → C(f(x1))
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
C(c(x1)) → D(d(d(x1)))
D(d(x1)) → C(f(x1))
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))
D(d(x0)) → C(a(g(x0)))
↳ QTRS
↳ QTRS Reverse
↳ QTRS Reverse
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ DependencyGraphProof
C(c(x1)) → D(d(d(x1)))
D(d(x0)) → C(a(g(x0)))
b(b(x1)) → c(d(x1))
c(c(x1)) → d(d(d(x1)))
c(x1) → g(x1)
d(d(x1)) → c(f(x1))
d(d(d(x1))) → g(c(x1))
f(x1) → a(g(x1))
g(x1) → d(a(b(x1)))
g(g(x1)) → b(c(x1))